Policy communication in the implementation of the Keluarga Sasaran Jaminan Perlindungan Sosial program in the City of Yogyakarta - Marita Ahdiyana; Arum Diyan Sukmawati (Universitas Negeri Yogyakarta, 2022)
Policy makers and implementers need to consider a good communication strategy as an instrument to support effective policy implementation. This article aims to analyze policy communication in the implementation of Social Security Target Families in Yogyakarta City. The research design used is descriptive qualitative. The results showed that the process of delivering information, clarity of information, and consistency of information have been able to support the successful implementation of the policy. Submission of information to policy implementers has been carried out through regular coordination meetings. Meanwhile, the delivery of information to the target group is carried out through socialization through television media and mass media coverage. The understanding and competence of policy implementers in their duties also supports this process. Clarity of information on policy implementation has been determined in the regulations that guide program implementation. One of them is the use of seven aspects and sixteen parameters in program data collection. In addition, it has also involved the community in the process, although there are still issues of likes and dislikes in data collection. The consistent application of regulations, orders, and information has also made it easier for implementers to apply policies in the field.